Prevalence of general and abdominal obesity among adolescents attending independent schools in Qatar. Issue 4 (12th December 2018) - Kerkadi, Abdelhamid; Hassan, Abdelmonem Sadig; Al Thani, Al Anoud Mohammed; Al Chetachi, Walaa; Akram, Hammad; Bawadi, Hiba; Vinodson, Benjamin; Risk, Nassar Moustafa Ragheb
Abstract : Purpose: The purpose of this paper is to determine the prevalence of general and abdominal obesity among adolescents attending independent schools in Qatar. Design/methodology/approaches: A school-based cross-sectional study was conducted in November-December 2013 in 23 secondary schools. A total of 1, 161 students aged 14 to 19 year olds were randomly selected using a multistage stratified cluster random sampling technique. Body weight, height and waist circumference (WC) were measured using standard protocol. The International Obesity Task Force (IOTF) age- and sex-specific body mass index (BMI) reference were used to define overweight and obesity. Abdominal obesity (AO) was defined by waist to height ratio (WHtR ≥ 0.5) and by sex- and age-specific WC cut-off values. Findings: The prevalence of overweight and obesity among the study population was 20.6 and 20.7%, respectively. The highest rate of overweight and obesity was observed among boys, and the youngest age group. The rate of obesity defined by either WC/or WHtR was higher than that assessed by BMI. The prevalence of AO assessed by WC and WHtR was 48.8 and 46.9%, respectively. The rate of AO was significantly higher ( p < 0.05) among boys compared to girls for both assessment criteria. The proportion of adolescents with AO (WHtR ≥ 0.5) according to BMI was 17.3%, 80.8% and 97.1% for adolescents with normal, overweight and obesity had AO, respectively. Being male was significantly associated with higher odds of having both general obesity and AO. Originality/value: The study revealed a high prevalence of general and abdominal obesity in adolescents in Qatar. Waist measures appear to be an important indicator in identifying adolescents at risk and should be included as screening tools for cardiometabolic risk.